1541. Infectious Complications in Adult Patients with Hemophagocytic Lymphohistiocytosis: A Single-Center Experience. (26th November 2018) - Nelson, Joanna; Martin, Beth; Lau, Eric; Ho, Dora
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare hematologic disorder which is characterized by excessive immune activation. In adults, it is typically secondary to an underlying process such as autoimmune disease, infection, or malignancy. Guidelines based on expert opinion suggest prophylaxis (PPX) with antiviral, antibacterial, and/or antifungal agents for patients undergoing treatment for HLH; however, the incidence of infectious complications is not known. We aimed to study the scope of infection in patients with HLH to help determine the best strategy for antimicrobial PPX. Methods: We performed a retrospective chart review of 56 adult patients who fulfilled clinical diagnostic criteria for HLH treated at Stanford University Hospital between 2012 and 2018. Infections diagnosed up to 1 month prior and up to 6 months after a diagnosis of HLH were reviewed. Results: A total of 57 episodes of HLH in 56 patients were reviewed. Infection was determined to be the trigger of HLH in five cases (EBV in three cases, Histoplasma in one case, MAC or HHV6 in one case). Antiviral PPX was used in 72%, PCP PPX in 75%, and antifungal PPX in 77% of HLH episodes. At least one infectious complication occurred in 33 of 57 episodes of HLH (58%) with 69 total infections diagnosed after HLH diagnosis: 46 bacterial, 12 viral, and 11 fungal. Bacterial infections included bacteremia (43%), pneumonia (15%), skin and soft tissue (13%), intra-abdominal infection (11%), urinary tract infection (13%), and others (5%). Of the viral infections, CMV viremia was the most prevalent and occurred in four patients (7% of HLH episodes). Fungal infections occurred in 19% of HLH episodes and included four yeast and seven mold infections (five proven and two possible). Three of these cases were not receiving antifungal PPX prior to infection; the remaining eight were breakthrough infections. Conclusion: Infectious complications of HLH are common, and likely result from a combination of host immune factors related to underlying disease and induced by immunosuppressive chemotherapy. Most noteworthy is the incidence of fungal infections which supports the use of antifungal PPX in this patient population. Even with this, breakthrough infection, including with opportunistic molds, is not uncommon. Disclosures: All authors: No reported disclosures.